2018
DOI: 10.1128/iai.00888-17
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Eimeria tenella Expressing Profilin of Eimeria maxima Elicits Enhanced Protective Immunity and Alters Gut Microbiome of Chickens

Abstract: Coccidiosis is one of the most serious diseases of livestock and birds in the world. Vaccination with live-parasite anticoccidial vaccines with genetic manipulation improving the immunogenicity of vaccine strains would be the best means for controlling coccidiosis in breeder and layer stocks, even in fast-growing broilers. Profilin from apicomplexan parasites is the first molecularly defined ligand for Toll-like receptor 11 (TLR11) and TLR12 in mice and is a potential molecular adjuvant. Here, we constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
(58 reference statements)
0
29
0
Order By: Relevance
“…The expression cassette was controlled by the EtSAG13 ( E. tenella surface antigen 13) promoter (Fig. 1a) [25]. Eimeria tenella sporozoites were transfected with the linearized pSDEP2AAMA1S plasmid and then inoculated into the cloacal opening of chicks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression cassette was controlled by the EtSAG13 ( E. tenella surface antigen 13) promoter (Fig. 1a) [25]. Eimeria tenella sporozoites were transfected with the linearized pSDEP2AAMA1S plasmid and then inoculated into the cloacal opening of chicks.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions include but are not limited to: (i) using advanced biotechnological tools to discover new immunodominant antigen(s) of Eimeria , such as IMP1 [26]; (ii) improving the heterologous antigen expression level by using a stronger promoter or increasing the gene copy number, etc. [24]; (iii) co-expressing multiple immunodominant antigens mediated by P2A in one recombinant Eimeria line or by double or multiple expression cassette [24, 39]; (iv) optimizing the antigens’ location in recombinant Eimeria for efficient recognition by host immune system [18]; and (v) fusion expression of heterologous antigens with cytokine(s) or other molecular adjuvants [21, 25, 40].…”
Section: Discussionmentioning
confidence: 99%
“…With its distinct biology and immunology, the Eimeria parasite also holds promise as a model organism for protozoan research. The establishment of transient transfection and stable selection protocols has greatly enhanced dissection of several biological and immunological properties in this parasite [2,3]. Nevertheless, the absence of an effective gene editing system has left many questions about functions of Eimeria's unique genes unanswered.…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
“…Recombinant Eimeria-expressing immunoglobulin Fc fragment with surface display that is fused with the glycosylphosphatidylinositol (GPI) anchor at its C terminus also enhances the protection of chickens against wild-type Eimeria infection (53). It was found that antigen derived from immunogenic species of Eimeria can serve as an adjuvant enhancing the immunogenicity of other Eimeria species, i.e., recombinant E. tenella expressing E. maxima profilin increases the immunogenicity of E. tenella, which elicits stronger cell-mediated immunity and provides better protection against E. tenella infection (54). All these findings indicate that it is feasible to genetically modify Eimeria for use as a novel vaccine vector and a safe and efficient coccidiosis vaccine.…”
Section: Modification Of Eimeria For Use As a Vaccine Vector And Beyondmentioning
confidence: 99%